Employing James Gee’s Analytic Lens for Identity to Investigate Teacher Identity Development - Shagufta Moghal, Asma Shahid Kazi, Fakhra Aziz (PJE, 2023)
The current article is an exploration of the construction and development of teacher identities at the tertiary level in Pakistan. Identity is the sense of who one is as a professional, and it is becoming evident that it is important for teachers at all levels to develop a clear sense of identity which is at harmony with their inner sense of self and personal values. There is evidence that successful identity construction leads to better practices and high level of commitment to the profession.